2017
DOI: 10.1111/jocn.13781
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of physical activity for community‐dwelling patients with hypertension

Abstract: The findings implied that hypertensive patients who did insufficient physical activity were subgroups that needed specific instructions in physical activity and motivation to take part in physical activity. Nurses should consider providing counselling and supervision to these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
1
7
1
Order By: Relevance
“…It is believed that patients could achieve a better outcome of BP control if they follow health expertise advice on hypertension treatment and healthy lifestyles in terms of exercising properly [33], avoiding smoking and drinking [34]. Supported by previous study reports, our hypothesis is that community-based BP monitoring has a positive effect on hypertension control through medication treatment and healthy lifestyle establishment.…”
Section: Introductionmentioning
confidence: 90%
“…It is believed that patients could achieve a better outcome of BP control if they follow health expertise advice on hypertension treatment and healthy lifestyles in terms of exercising properly [33], avoiding smoking and drinking [34]. Supported by previous study reports, our hypothesis is that community-based BP monitoring has a positive effect on hypertension control through medication treatment and healthy lifestyle establishment.…”
Section: Introductionmentioning
confidence: 90%
“…Recent research on the future health of the elderly population and improvements in quality of life has received a great deal of attention, and the relevance of physical exercise has been highlighted in these studies (5,6). To be able to understand their needs, it is important to assess the level of physical activity in the elderly (7)(8)(9). Questionnaires, diaries, accelerometers, and pedometers are some of the tools that can be used to assess physical activity in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important for these methods to be suitable for the elderly and to be standardized. There are scales that have been developed specifically for the elderly to deal with such problems and achieve more reliable results, and these scales are similar in content to each other (8)(9)(10). The Physical Activity Scale for the Elderly (PASE) was developed in 1993 by Washburn et al (11), and the validity and reliability study of the Turkish version of PASE was conducted by Ayvat et al (12).…”
Section: Introductionmentioning
confidence: 99%
“…At meantime, hypertensive people appear to be less physically active than those without hypertension [12]. It is reported that only about one third of hypertensive patients achieve the recommended PA level [13]. Most previous researches subdivided physical activity by domains (e.g., occupational, domestic and leisure-time activity) [14] or intensities (e.g., light, moderate and vigorous physical activities) when exploring the relationship between PA and CVDs [15].…”
Section: Introductionmentioning
confidence: 99%